¿Están los bogotanos interesados en vivir cerca de un parque urbano? - Penagos Concha, Angela María (Sociedad y Economía, 2005)
This paper intends to underline the economic importance of construction and maintenance of urban parks in the city of Bogotá in order to produce evidence to defender the public domain and demónstrate that there is an interest among Bogotanos for the urban parks. For this purpose the realty market information of Bogotá was used and the housing prices were analyzed in function of the different housing characteristics, among them, the vicinity to urban parks. The results point to the fact that housing in Bogotá are positively affected by urban parks. However, urban parks of social types have the most salientinfluence.